Developments in Combustion Technology 2016
DOI: 10.5772/64761
|View full text |Cite
|
Sign up to set email alerts
|

Solution Combustion Synthesis: Applications in Oxide Electronics

Abstract: Oxide-based electronics have been well established as an alternative to silicon technology; however, typical processing requires complex, high-vacuum equipment, which is a major drawback, particularly when targeting low-cost applications. The possibility to deposit the materials by low-cost techniques such as inkjet printing has drawn tremendous interest in solution processible materials for electronic applications; however, high processing temperatures still required. To overcome this issue, solution combusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Where the RV/OV ratio is equal to Σ (coefficients of the reducing elements vs. valencies)/ Σ (coefficients of the oxidant elements vs. valences), 18 n is the number of moles of reducer/mole of the oxidant. 72 During calculation, nitrogen and oxygen oxidizer elements should have 0 and −2 valances, respectively. Carbon and hydrogen reducing elements should have +1 and +4 valances and water is not incorporated in this calculation.…”
Section: Solution Combustion Synthesismentioning
confidence: 99%
“…Where the RV/OV ratio is equal to Σ (coefficients of the reducing elements vs. valencies)/ Σ (coefficients of the oxidant elements vs. valences), 18 n is the number of moles of reducer/mole of the oxidant. 72 During calculation, nitrogen and oxygen oxidizer elements should have 0 and −2 valances, respectively. Carbon and hydrogen reducing elements should have +1 and +4 valances and water is not incorporated in this calculation.…”
Section: Solution Combustion Synthesismentioning
confidence: 99%
“…Several studies have reported the production of ZrO 2 nanomaterials using sol-gel, particularly solution combustion synthesis, which is included in the sol-gel method [58][59][60]. Solution combustion synthesis is an attractive technique for the preparation of ZrO 2 nanopowders and thin films, owing to its simplicity, energy and time savings, cost-effectiveness, versatility, higher purity compared with conventional sol-gel methods, low synthesis temperatures, and compatibility with flexible substrates and large scale production [61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…The metal precursors are the source of the metal cations which decides the final metal oxide. One of the methods for the synthesis of zirconia nanopowders is by annealing stochiometric mixtures of zirconium oxy nitrate hydrate in alcohol and urea [33]. Nanocrystalline zirconium oxide powder has been prepared by the glowing combustion method using sucrose as the fuel and zirconyl nitrate as an oxidant in aqueous solution [34].…”
Section: Solution Combustion Synthesis (Csc)mentioning
confidence: 99%